Implementation of Process Standardization for Vault 4 and 5 of Cellars at Jasper Hill Farm in Greensboro Vermont USA. (2023)
Cellars at Jasper Hill Farm is a cheese factory located in the Northeast region of the United States; it is an industrial company dedicated to producing award-winning and high quality cheeses. This company has sought ways to increase the value of milk in the state of Vermont by producing high-quality cheeses. During the development of the international internship, the intern will develop a proposal to improve a particular company's problem in the production area. During the first month of the international internship, the intern will recognize the processes and products that the company has, while learning the company's health standards and organizational culture. Subsequently, he will propose a defined general objective that allows solving the company's problems in the production area, specifically in the packaging process of Vault 4 and 5; this must include engineering tools learned through the University. The intern will analyze the current tools that the company is using and through a bibliographic search process, will propose engineering tools and methods that can help to improve the process or solve the problem. The company will evaluate the proposal presented by the intern and verify if it is viable through a feasibility analysis, which must show the benefits of the improvement and clearly explain why implementing the selected engineering tool is necessary. The improvement will seek the standardization of the packaging processes known in the company as P2P, using engineering tools to improve and optimize processes. These include user stories, creating indicators for control and evaluation, and process diagramming through the Bizagi Modeler program.